2021
DOI: 10.1101/2021.06.13.21258851
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

VAERS data reveals no increased risk of neuroautoimmune adverse events from COVID-19 vaccines

Abstract: Neuroautoimmune disorders, such as multiple sclerosis and Guillain-Barre syndrome, have been documented in relation to various vaccines in the past. This paper uses passive reporting information from the CDC/FDA's VAERS system to analyse whether neuroautoimmune presentations are reported at a relatively higher or lower rate, vis-a-vis other adverse effects, for COVID-19 vaccines than for other vaccines. Through computing the reporting odds ratios for a range of symptoms and comparator vaccines, a clear indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Previous research has suggested a range of neuro-immune mediated COVID-19 vaccine responses, although the link to neuro-autoimmunity is not clear (Csefalvay, 2021). To our knowledge, the role of vitamin B12 deficiency has not been properly investigated as part of these responses.…”
Section: Discussionmentioning
confidence: 96%
“…Previous research has suggested a range of neuro-immune mediated COVID-19 vaccine responses, although the link to neuro-autoimmunity is not clear (Csefalvay, 2021). To our knowledge, the role of vitamin B12 deficiency has not been properly investigated as part of these responses.…”
Section: Discussionmentioning
confidence: 96%
“…As of September 2021, VAERS database had 328 reports of suspected cases of TM worldwide, following all types of vaccines ( von Csefalvay, 2021 ). However, a recent analysis of VAERS data revealed no increased risk of neuroautoimmune adverse events from COVID-19 vaccines compared to other vaccines ( Beh et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…This confirms previous findings as to the safety of COVID-19 vaccines with respect to neuroautoimmune AEFIs. [12] Only three specific autoimmune aetiologies exceed the reporting odds ratio of 2.0, which is widely considered the minimum for signal generation in passive pharmacovigilance. Psoriasis (ROR = 2.99, p < 0.001, 95% CI: 2.34-3.82) and myasthenia gravis (ROR = 3.90, p < 0.001, 95% CI: 2.63-5.80) were observed with a somewhat elevated ROR vis-a-vis other vaccines and other potential AEFIs.…”
Section: Resultsmentioning
confidence: 99%
“…This study confirms previous findings as to the safety of the COVID-19 vaccine with regard to neuroautoimmune disorders. [12] In particular, with respect to Guillain-Barre syndrome, patients were three times as likely to have received a non-COVID-19 vaccine than a COVID-19 vaccine. The absence of a neuroautoimmune safety signal may be usefully emphasised in reassuring the population about the COVID-19 vaccines, especially considering the prominent position such side effects occupy in the landscape of concerns about vaccines that drive vaccine hesitancy.…”
Section: Neuroautoimmune Aefismentioning
confidence: 98%
See 1 more Smart Citation